2016
DOI: 10.1136/lupus-2015-000118
|View full text |Cite
|
Sign up to set email alerts
|

Response to belimumab among patients with systemic lupus erythematosus in clinical practice settings: 24-month results from the OBSErve study in the USA

Abstract: ObjectiveTo examine disease activity and clinical outcomes, and describe overall patterns of systemic lupus erythematosus (SLE) care in patients who received belimumab in a real-world clinical setting.MethodsThis observational cohort study was conducted in US clinical practices. Rheumatologists (n=92) identified adults with SLE who had received ≥8 infusions of belimumab plus standard of care (SoC). Physicians assessed disease outcomes at 6-month intervals using patient medical charts, for up to 24 months. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
95
3
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(127 citation statements)
references
References 9 publications
22
95
3
7
Order By: Relevance
“…Data on 195 patients show response to belimumab at 3 and 6 months post-initation to be consistent with those reported in the phase III trials, with 48% of patients responding clinically by 3 months and 58% of patients by 6 months [Hui-Yuen et al 2014]. A similar observational study of 384 SLE patients over 12 months revealed sustained efficacy of belimumab after 12 months of use and allowed for tapering of corticosteroid dose [Collins et al 2013]. However, six patients were also started on corticosteroids during the study.…”
Section: Real-world Usesupporting
confidence: 63%
“…Data on 195 patients show response to belimumab at 3 and 6 months post-initation to be consistent with those reported in the phase III trials, with 48% of patients responding clinically by 3 months and 58% of patients by 6 months [Hui-Yuen et al 2014]. A similar observational study of 384 SLE patients over 12 months revealed sustained efficacy of belimumab after 12 months of use and allowed for tapering of corticosteroid dose [Collins et al 2013]. However, six patients were also started on corticosteroids during the study.…”
Section: Real-world Usesupporting
confidence: 63%
“…Since its approval by the FDA, "real-world" clinical experience with belimumab has largely been positive [61][62][63]. Also since approval of belimumab as an IV drug, a randomized, double-blind, placebo-controlled trial of belimumab (200 mg fixed dose SC weekly through week 52) plus SOC in SLE demonstrated a statistically significantly greater response rate among belimumab-treated subjects than among placebo-treated subjects [64].…”
Section: ) Belimumabmentioning
confidence: 99%
“…Importantly, as a reduction in SLE flares was extensively reported [2][3][4][5][6][7][8], it looks advisable to prompt belimumab especially in patients displaying a relapsing-remitting disease pattern, in whom a significant decrease in flare rate is among the fundamental treatment goals.…”
Section: Expert Opinionmentioning
confidence: 99%
“…Importantly, relevant real-life experience [4,6,7,9] as well as a 7-year long-term extension study involving patients coming from the phase 2 RCT who had had an improvement in physician global assessment (PGA) since baseline proved a long-standing disease control and decrease in flare rate during the overall 7-year observation on belimumab treatment [17], suggesting such positive effects are long-lasting. Notably, published studies including RCT, long-term extensions studies and real-life experience underlined a good safety and tolerability profile of belimumub use even when added to immunosuppressive therapy.…”
Section: Observations On Belimumab Use In Clinical Practicementioning
confidence: 99%
See 1 more Smart Citation